2020
DOI: 10.3390/ani10101720
|View full text |Cite
|
Sign up to set email alerts
|

Coat Color and Cat Outcomes in an Urban U.S. Shelter

Abstract: Some nonhuman animal shelters have developed rehoming programs for black cats to remedy what they believe are their higher rates of euthanasia and lower rates of adoption. This study reviews humans’ preferences/aversions to cats of various coat colors and uses contingency tables and multinomial logistic regression to test possible differences in outcomes (euthanasia, adoption, or transfer) for 7983 cats that entered an urban public shelter in Kentucky, USA from 2010 through 2011. While coat color overall was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Contextualizing the findings of any coat color study with the existing literature is not simple due to the lack of uniform color patterning in cats [12]. The results of the present study partially coincide with those found by Delgado et al [10], who reported that orange cats are considered friendly and tricolor cats are intolerant.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Contextualizing the findings of any coat color study with the existing literature is not simple due to the lack of uniform color patterning in cats [12]. The results of the present study partially coincide with those found by Delgado et al [10], who reported that orange cats are considered friendly and tricolor cats are intolerant.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, color classifications are prone to errors. Carini et al [12] indicated that coat color in cats is difficult to describe due to the wide variety of patterns that exist. Therefore, color assessment is subjective and results in incongruity between the findings of different studies on the subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have tried to identify adopter ‘preferences’ and other factors that may decrease LOS, often focusing on ‘phenotypic’ traits of animals such as breed group, sex, size, coat colour and age as listed in shelter databases. For example, Lepper et al ( 2002 ), Brown et al ( 2013 ), Brown and Morgan ( 2015 ), Kay et al ( 2018 ) and Voslářová et al ( 2019 ) used statistical analyses to compare animal traits to LOS, live-release rate (Patronek & Crowe 2018 ) or general outcomes of adopted, euthanased or transferred (Carini et al 2020 ). A common finding from such analyses is that younger dogs have a shorter LOS than adults (Brown et al 2013 ; Žák et al 2015 ; Patronek & Crowe 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Identifying predictive components which result in different outcomes are vital, and typically, the focus is on characteristics of the cats as well as the type of intake. Regarding the physical attributes of the cat, coat color is considered a strong predictor of adoption ( 11 – 13 ). Age is a prominent factor as well, where younger cats are more likely to be adopted than older cats ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%